FAUNA IKAN DI SUNGAI CIKANIKI, TAMAN NASIONAL GUNUNG HALIMUN Fish Fauna in Cikanini River, Mount Halimun National Park - Rachmatika, Ike (Research Center for Biology-Indonesian Institute of Sciences, 1998)
-